Dynamic Association between Non-Renewable Energy Matrix, Carbon Dioxide Emissions, and Economic Growth in G7 Countries: A Contribution to the Sustainable Development Goals - Martins, Tailon; Castro Barreto, Alisson; Reichert, Bianca; Mendonça Souza, Francisca; Vicini, Lorena; Mendonça Souza, Adriano (International Journal of Energy Economics and Policy, 2025)
This study contributes to the Sustainable Development Goals (SDGs) and the 2030 Agenda by examining CO2 emissions and economic growth in G7 countries. The primary aim is to explore connections among coal, oil, and natural gas consumption, predicting both CO2 emissions and economic growth despite external disruptions. The research employs vector autoregressive (VAR) and Bayesian autoregressive (BVAR) models, alongside the Granger causality test. The study tests hypotheses: (i) Fossil fuel consumption drives CO2 emissions; (ii) Fossil fuel consumption influences economic growth; (iii) A causal link exists between CO2 emissions and economic growth. Air pollution analysis (hypothesis i) indicates natural gas associates with CO2 emissions in Germany, the USA, and Italy; coal links to CO2 emissions in Canada, the USA, and Japan; CO2 emissions due to oil connect to Canada, the USA, France, Italy, Japan, and the UK. Hypothesis ii shows natural gas consumption in Canada, the USA, France, Italy, and coal consumption in France, Italy, and the UK correlate with GDP. No GDP correlation with oil consumption is seen. Hypothesis iii reveals a two-way relationship only in Germany CO2 emissions impact GDP and vice versa. Forecasts suggest external shocks lead to variable fluctuations up to seven periods ahead.